Militancia política y ficción literaria en la narrativa de Carlos Montenegro - Gallardo-Saborido, Emilio J. (Revista de Letras, 2017)
The author Carlos Montenegro (Pobra do Caramiñal, 1900-Miami, 1981) joined in 1933 the Cuban Communist Party. He was a member of it until 1941 when he was expelled after applying for his resignation. This paper analyses the relationships between political commitment and literature in Montenegro’s production of this period. During these years, this writer expressed his ideological commitment in several ways. Apart from fictional narrative, he resorted to other genres as testimonial, in Tres meses con las fuerzas de choque (División Campesino) -1938; or theatre, with works as Los perros de Radziwill -1939 and Tururí ñan ñan -1939. Particularly, this contribution focused on the ideological and literary analysis of his book of short stories Dos barcos -1934. There the political commitment motif appears as one the axial topics of the volume.